Foreign Direct Investment and Economic Growth: Evidence from OECD Countries (2010-2023) - Kilaj, Duresa; Gajraku, Ardita; Nimani, Bleona; Misiri, Valdrin (Sustainable Governance in the Age of Artificial Intelligence: Interdisciplinary Perspectives on ESG, Digital Transformation and Corporate Responsibility, 2026)
This study analyzes the impact of foreign direct investment (FDI) on economic growth in OECD countries, using secondary data from the World Bank, International Monetary Fund, and OECD for 2010–2023. For empirical analysis, fixed- and random-effects models, as well as multiple linear regression, were employed. The results show that FDI, trade openness, and inflation positively influence economic growth, whereas government expenditures negatively affect it, highlighting the need for improved public financial management. Consequently, the study recommends that policymakers shift public spending to productive investments and adopt strategies that promote long-term growth and sustainability. The originality of this study stems from the use of reliable data and empirical analysis focused on developed OECD countries.